Maize Intercropping in the Traditional “Milpa” System. Physiological, Morphological, and Agronomical Parameters under Induced Warming: Evidence of related Effect of Climate Change in San Luis Potosí (Mexico) - Idrissa Diédhiou; Hugo M. Ramírez-Tobias; Javier Fortanelli-Martinez; Rogelio Flores-Ramírez (Life, 2022)
Warmer temperatures predicted as a result of climate change will have an impact on milpa. An experiment was carried out with induced passive heat with the objective of simulating the increase in temperature on the physiological, morphological, and yield parameters of milpa from different climates of San Luis Potosí, Mexico. Two different environments, Open-top chambers (OTC) and control, and three milpas, from warm–dry, temperate, and hot and humid climates, were studied. A total of 12 experimental units of 13.13 m2 were used in the random design, with a factorial arrangement of 2 × 3 and two replications. Abiotic variables (minimum, maximum, and mean daily temperatures and accumulated heat units) were determined and compared between the two environments and confirmed that the OTC increased the abiotic variables. The growth and development parameters increased under the warming effect. Furthermore, the milpa from hot and humid climate was the least affected. In contrast, the warming considerably delayed yield parameters. The squash suffered the most, while the bean benefited the most. The warming affected the chlorophyll fluorescence and gas exchange differently for each crop. However, at an early stage, the maximum photochemical efficiency (Fv/Fm) and non-photochemical quenching (qN) for bean and maize were reduced, while at a late stage, they were Fv/Fm, photochemical quenching (qP), and qN for maize; stomatal conductance and transpiration rate of the squash were improved under the warming treatments. In conclusion, the warming delayed the yield and photosynthetic parameters, while growth and development benefited. The milpa systems were differently affected by warming.